PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT YEAKIN PLASTIC INDUSTRY BATAM - Malau, Bergiat; Wasiman, Wasiman (SCIENTIA JOURNAL, 2019)
The purpose of this research is to find out and analyze compensation and motivation on performance of employees at PT Yeakin Plastic Industry Batam as well as searching for variables which influence. The results of the analysis using SPSS Version 20 showed that compensation and motivation of a positive effect on performance of employees. The test results with the Test t note that variable compensation is the variable that influence positively and significantly to the performance of the employees at PT Yeakin Plastic Industry Batam. From the explanation above, the authors suggest that the compensation given to employees should be appropriate and just in time so that the beliefs of the employees against the company is getting bigger, quietness and concentration will work better, so employees will feel more satisfied in their work as well as it can improve the performance of employees. The motivation given to employees should be more thrust in again and give a positive referral referral to the employee, in which case the grant awards, attention, competition, participation, pride and punishment are treated equitably on the each of the employees. So there happen to social jealousy between employees and can improve the performance of employees. Satisfy the granting of compensation and motivation of the good will of course enhance the productivity and performance of employees increased.